Enzyme‐Instructed Self‐Assembly (EISA) and Hydrogelation of Peptides. Issue 3 (24th April 2019) - Gao, Jie; Zhan, Jie; Yang, Zhimou
Abstract: Self‐assembly is a powerful tool for constructing supramolecular materials for many applications, ranging from energy harvesting to biomedicine. Among the methods to prepare supramolecular materials for biomedical applications, enzyme‐instructed self‐assembly (EISA) has several advantages. Herein, the unique properties and advantages of EISA in preparing biofunctional supramolecular nanomaterials and hydrogels from peptides are highlighted. EISA can trigger molecular self‐assembly in situ. Therefore, using overexpression enzymes in disease sites, supramolecular materials can be formed in situ to improve the selectivity and efficacy of the treatment. The precursor may be involved during the EISA process, and it is actually a two‐component self‐assembly process. The precursor can help to stabilize the assembled nanostructures of hydrophobic peptides formed by EISA. More importantly, the precursor may determine the outcome of molecular self‐assembly. Recently, it was also observed that EISA can kinetically control the peptide folding and morphology and cellular uptake behavior of supramolecular nanomaterials. With the combination of other methods to trigger molecular self‐assembly, researchers can form supramolecular nanomaterials in a more precise mode and sometimes under spatiotemporal control. EISA is a powerful and unique methodology to prepare supramolecular biofunctional materials that cannot be generated from other common methods. Abstract : Enzyme‐instructed self‐assembly (EISA) has several unique properties and advantages in preparing biofunctional supramolecular nanomaterials from peptides. Recent progress in this area is reviewed, with a focus on in situ EISA, precursor involved EISA, controlling peptide folding by EISA, and the combination of other methods with EISA. The perspectives and challenges are also discussed.